A Spatial Analysis of Thăng Long Capital During the Lý Period Through Re-Exploitation of Written Sources. Issue 1 (3rd February 2014) - Momoki, Shiro
Abstract In August 2010, the Vietnamese government and people celebrated the 1000th anniversary of the establishment of their capital Thăng Long (present-day Hanoi). Historical research on Thang Long has progressed considerably over the past decade, especially since the '18 Hoàng Diệu' archaeological site was found. As a specialist in the Ly-Tran Period, I offer this contribution to the study of the spatial composition of Thăng Long Capital under the Ly dynasty (AD 1010–1226), through a re-examination of written sources such as dynastic annals. In view of the various functions necessary for a capital, new questions need to be addressed based on the original texts of the sources and the theories of East Asian ancient capitals. For instance: 1) were the cam trung ('inside the forbidden area') and dai noi ('great interior area') the same or not? 2) thanh ('wall') and thanh noi ('inside the wall'?) are often mentioned in the sources, but which wall of the capital was it? 3) In China, the outermost area of the capital was not always included in the thanh (cheng) area; did the system of 'three concentric walls' indeed exist in Đại Việt during the Ly-Tran Period? And, 4) what functions and meanings did the space within each wall (and the suburban area outside the outmost wall) have? Given the present condition of sources, it is difficult to answer these questions. In this article I offer some tentative remarks in an attempt to fix a steady base for future collaborative research between historians and archaeologists.